Cost‐Effectiveness Analysis of Two Rituximab Retreatment Regimens for Longstanding Rheumatoid Arthritis. Issue 7 (July 2015) - Quartuccio, Luca; di Bidino, Rossella; Ruggeri, Matteo; Schiavon, Franco; Biasi, Domenico; Adami, Silvano; Punzi, Leonardo; Cicchetti, Americo; de Vita, Salvatore
<x xml:space="preserve">Abstract</x> Objective Rituximab (RTX) is licensed for second‐line treatment of rheumatoid arthritis (RA) after first tumor necrosis factor (TNF) inhibitor failure. RTX is generally administered intravenously at 1 gm 2 weeks apart, and the retreatment is scheduled at the time of clinical relapse (regimen 1). A more intensive regimen is proposed with a fixed full cycle after 6 months (regimen 2) if remission is not reached. A cost‐effectiveness analysis (CEA) compared these 2 regimens of RTX administration in patients with longstanding RA based on data provided by an observational study. Methods An observational retrospective study was conducted on 102 patients, enrolled in 3 hospitals and followed for ≥12 months. Forty‐seven patients followed regimen 1, while 55 patients followed regimen 2. A CEA based on a Markov model was conducted. A lifelong and social perspective was adopted. CEA was conducted for the entire cohort and for the 2 subgroups separately (patients with positive rheumatoid factor and/or anti–cyclic citrullinated peptide and failures to TNF inhibitors). Results Results for the overall sample show at 10, 20, and 30 years that regimen 1 is less costly and associated with a higher quality of life compared to regimen 2. Probabilistic sensitivity analysis at 10 years estimated a probability of 95.1% for regimen 1 to be cost effective given a willingness to pay of €35, 000/quality‐adjusted life year, while for seropositive patients and for TNF failures it was estimated to be 92% and 92.7%, respectively. Conclusion In longstanding RA, cost effectiveness of RTX retreatment at clinical relapse was found to be at least equivalent to the more intensive regimen proposed.